ANALYSIS OF LIVESTOCK RESOURCE ALLOCATION IN CATTLE BUSINESS DEVELOPMENT - Sintya J K Umboh; Boyke Rorimpandey; Merci R Waani (Journal Publicuho, 2024)
The economic performance of farmers’ households shows the allocation of resources owned by households for productive, consumptive, and investment activities. The largest allocation for cattle business illustrates the responsibility of farmers’ households in using resources for their goals. The research used a survey method. Then, the data collection technique employed interviews with respondents from cattle farmers' households by using the designated questionnaire. The sampling method was purposive, which was the population of cattle farmers’ households receiving capital assistance for cattle business and selling their cattle from capital assistance. The resource allocation for the cattle business was significantly influenced by the total of the received capital assistance, the value of calves, and the allocation of capital assistance for non-cattle businesses.